Integrating Resilience, Agility, and Sustainability into Future Validated Supply Chains - Lilechi, Melvine Chepkoech (Journal of Global Economy, Business and Finance, 2025)
Futuristic supply chain officers now have a unique opportunity to future - proof their supply chains by recognizing and integrating three new priorities: resilience, agility, and sustainability. Traditionally focused on cost, capital, quality, and service, supply chains must now also address the challenges of disruption, meet rapidly evolving customer needs, and support a clean, socially just economy. Historical examples, such as Toyotas rapid recovery post - disaster and Nikes technological advancements during the COVID - 19 pandemic, illustrate the importance of these new priorities. Agile supply chains leverage digital technologies, smart automation, and skilled, flexible teams to enhance responsiveness and adaptability. Successful integration of these priorities requires a foundational redesign of supply chain strategies, with a shift in mindset towards comprehensive risk management, agility, and sustainability metrics alongside traditional performance indicators.